2015
DOI: 10.11604/pamj.2015.20.108.4831
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with low birth weight among neonates born at Olkalou District Hospital, Central Region, Kenya

Abstract: IntroductionNinety-two percent of Low Birth Weight(LBW) infants are born in developing countries, 70% in Asia and 22% in Africa. WHO and UNICEF estimate LBW in Kenya as11% and 6%by 2009 Kenya Demographic Health Survey. The same survey estimated LBW to be 5.5% in Central Province, Kenya. Data in Olkalou hospital indicated that prevalence of LBW was high. However, factors giving rise to the problem remained unknown.MethodsA cross-sectional analytic study was therefore conducted to estimate prevalence and distrib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

24
62
7
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(97 citation statements)
references
References 9 publications
24
62
7
4
Order By: Relevance
“…The finding of this study indicated that 19.53%, of neonates were born with low birth weight. The finding of this study is higher than the studies done in Northern Ethiopia (10%) (Gebregzabiherher, Haftu, Weldemariam, & Gebrehiwet, 2017), Axum and Laelay Maichew district (9.9%) (Teklehaimanot, Hailu, & Assefa, 2014), Kenya (12.3%) (Muchemi, Echoka, & Makokha, 2015), Northeast Nigeria16.9%, (Takai, Bukar, & Audu, 2014), Jakarta Indonesia (4. 5%) (Yanita, 2010), Nepal11.7% (Singh, Shrestha, & Marahatta, 2010), Iran (6.8%) (Jafari, Eftekhar, Pourreza, & Mousavi, 2010) and Abha City Saudi Arabia18.8%, (Baijayanti, Faten, & HAM, 2012).Whereas it is lower than studies done in Kersa, West Ethiopia (28.3 %) (Assefa, Berhane, & Worku, 2012) and Gambia (22.5%) (Jammeh, Sundby, & Vangen, 2011).…”
Section: Discussioncontrasting
confidence: 67%
“…The finding of this study indicated that 19.53%, of neonates were born with low birth weight. The finding of this study is higher than the studies done in Northern Ethiopia (10%) (Gebregzabiherher, Haftu, Weldemariam, & Gebrehiwet, 2017), Axum and Laelay Maichew district (9.9%) (Teklehaimanot, Hailu, & Assefa, 2014), Kenya (12.3%) (Muchemi, Echoka, & Makokha, 2015), Northeast Nigeria16.9%, (Takai, Bukar, & Audu, 2014), Jakarta Indonesia (4. 5%) (Yanita, 2010), Nepal11.7% (Singh, Shrestha, & Marahatta, 2010), Iran (6.8%) (Jafari, Eftekhar, Pourreza, & Mousavi, 2010) and Abha City Saudi Arabia18.8%, (Baijayanti, Faten, & HAM, 2012).Whereas it is lower than studies done in Kersa, West Ethiopia (28.3 %) (Assefa, Berhane, & Worku, 2012) and Gambia (22.5%) (Jammeh, Sundby, & Vangen, 2011).…”
Section: Discussioncontrasting
confidence: 67%
“…It is also lower than studies from northwest Ethiopia, Kenya and Zimbabwe [810]. The reason for this discrepancy may be the time this study is conducted and recent interventions in the prevention of LBW may have strengthen and contributed towards reduction in the incidence of LBW.…”
Section: Discussionmentioning
confidence: 67%
“…9,10 Worldwide, different epidemiological studies have reported varied prevalence rates in Kenya (12.3%), Tanzania (13.6% & 14%), Central Africa (9%-23%) and Chennai (25.8%). [11][12][13][14][15] Higher prevalence of low birth weight was reported in a study conducted in Nigeria (45%). 16 Studies in India have also showed varied prevalence rates of LBW, 21.8% in Assam, 36.8% in Madhya Pradesh, and 27.76% in Odisha.…”
Section: Current Scenario Of Lbwmentioning
confidence: 99%